The Relationship between Ferritin and Calcium Levels in Patients with Thalassemia β Major - Iskandar, Nurdin Aji; Salimo, Harsono; Moelyo, Annang Giri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Thalassemia is a hereditary disease in which the sufferer is unable to produce sufficient amounts of hemoglobin, causing impaired function of red blood cells and shortened red blood cell age. Thalassemia sufferers are spread all over the world, and thalassemia is one of the health problems in the world. Therapy in patients with thalassemia is with routine blood transfusions. One side effect of repeated transfusions is iron overload which causes deposits of iron in the endocrine glands. This study aimed to determine the relationship between ferritin levels with blood calcium levels in patients with β major thalassemia.Subjects and Method: This was a cross-sectional study conducted at Dr. Moewardi, Surakarta, from June to November 2017. Samples of 49 patients with thalassemia β major aged 5-10 years were selected using consecutive sampling. The dependent variable is blood calcium levels. The independent variable is ferritin level. Data were analyzed with Chi Square test.Results: High ferritin levels reduce calcium level in pediatric thalassemia β major patients, but not statistically significant (OR = 0.27; 95% CI = 0.04 to 1.64; p = 0.134).Conclusion: High ferritin levels decrease with calcium levels in pediatric thalassemia β major patients, but not statistically significant.Keywords: ferritin, calcium, thalassemia β majorCorrespondence: Andhika Trisna Putra. Department of Pediatrics, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hospital, Surakarta. Telpon/Fax.0271-633348, Email: andhika.pediatric@gmail.comIndonesian Journal of Medicine (2020), 05(02): 137-141https://doi.org/10.26911/theijmed.2020.05.02.07